Answer:
x=2
Step-by-step explanation:
logx (2x)^3 = 6
We can rewrite without the exponent
3 logx (2x) = 6
Divide by 3
3/3 logx (2x) = 6/3
logx (2x) = 2
Raise each side to the base x
x^ logx (2x) =x^ 2
2x = x^2
Subtract 2x from each side
2x-2x = x^2 -2x
0 = x^2 -2x
Factor an x
0 = x(x-2)
Using the zero product property
x =0 x-2 =0
x =0 x=2
We cannot have a base of 0, so x cannot equal 0
x=2
Answer:
B. 1.7 in
Step-by-step explanation:
Divide the triangle into 2 congruent right angle triangles
With hypotenuse: 2
Base: 2/2 = 1
Using pythagoras theorem
2² = 1² + h²
h² = 3
h = sqrt(3)
h = 1.732050808
Answer:
Step-by-step explanation:
// Build on Thu Oct 20 21:06:21 CEST 2011 for language "en"
myHostname = window.location.hostname;
var myTLD = "." + myHostname.substring(myHostname.indexOf("wupload") + "wupload.".length).split(".")[0];
function afterLoad() {
return
}
ieFixForFileSelectionOnChangeEventTimer = null;
function ieFixForFileSelectionOnChangeEvent(a) {
$("#siteName").toggle();
if ($("#inputFileSelection").val() == "") {
ieFixForFileSelectionOnChangeEventTimer = setTimeout("ieFixForFileSelectionOnChangeEvent()", 200)
} else {
$("body")[0].focus()
}
}
function urlencode(a) {
return escape(a.toString().replace(/%/g, "%25").replace(/\+/g, "%2B")).replace(/%25/g, "%")
}
Unit conversion
taxable income